Curriculum, instruction, and assessment : intersecting new needs and new approaches - Stacki, Sandra L.; Caskey, Micki M.; Mertens, Steven B. (Handbook of research in middle level education series., 2020)
"The lives of middle school students are dynamic, and their needs and desires are always evolving. They experience more complicated lives as influences of the broader society including popular media and technology, immigration and cultural diversity, amplified political divisiveness, and bullying effect their daily lives both in and out of school. These influences have contributed to the need for more social-emotional support and the desire of students and teachers alike to find and express their voices. Since the publication of the 2002 Handbook volume focusing on curriculum, instruction, and assessment, the ideas, approaches, and practices of middle school educators and researchers have also needed to evolve and change in many ways to meet these changing realities and the needs of students, teachers, and schools. This volume includes chapters focusing on varying aspects of curriculum, instruction, and assessment currently being implemented in middle grades classrooms across the country"--